2011
DOI: 10.2116/analsci.27.937
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Sensitive Assay of Gallic Acid Based on Localized Surface Plasmon Resonance Light Scattering of Silver Nanoparticles through Modified Tollens Process

Abstract: A simple, low toxic, sensitive strategy based on the localized surface plasmon resonance light scattering (LSPR-LS) properties of silver nanoparticles (AgNPs) is introduced for the detection of gallic acid (GA). It was found that the silver ammonium complex, [Ag(NH(3))(2)](+)(aq), could be reduced in the alkaline medium by GA at room temperature; this reaction formed dispersed AgNPs. Transmission electron microscopy analyses were performed to ascertain the formation of AgNPs. UV-visible spectra revealed the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Therefore, the accurate determination of GA is a very important concern for human health. To date, many methods have been developed for the determination of GA, such as flow injection analysis [5], resonance light scattering [6], reversed phase high-performance liquid chromatography (HPLC) [7], high-pressure liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (HPLC-ESI-QTOF-MS/MS) [2] electrochemical sensors and nano-structured sensors [1,[8][9][10]. Among these, electrochemical methods have received much attention lately, mainly due to their sensitivity, selectivity and simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accurate determination of GA is a very important concern for human health. To date, many methods have been developed for the determination of GA, such as flow injection analysis [5], resonance light scattering [6], reversed phase high-performance liquid chromatography (HPLC) [7], high-pressure liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (HPLC-ESI-QTOF-MS/MS) [2] electrochemical sensors and nano-structured sensors [1,[8][9][10]. Among these, electrochemical methods have received much attention lately, mainly due to their sensitivity, selectivity and simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…1. Recently, the potential application of nanoparticles for biological detection in Chinese medicine and the impact of nanoparticles on the luminescence of traditional Chinese medicine have gradually attracted the attention of investigators [26]. Therefore, as a new type of Chinese medicine fluorescence probe, osthole is selected as the chromophore to study the luminescence properties of osthole in the presence of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The Tollens process has been employed for many decades in the electroless deposition of silver to generate reective mirrors on the surface of solid supports. 24 The advantages of the present method against the traditional Tollens process for visualizing LFPs are that: (1) the modied Tollens process is simple and convenient; (2) the ink is stable for months, when stored in a sealed vial at 4 C; (3) this method enables in situ formation of AgNPs on the surfaces of many materials. 22 Furthermore, we found that the Tollens process cannot be used for visualization of LFPs even on glass slide, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%